Performance of buried HDPE pipes – part I: peaking deflection during initial backfilling process. Issue 4 (18th April 2017) - Zhou, M.; Du, Y. J.; Wang, F.; Liu, M. D.
Abstract : Peaking deflection caused by compacting the sidefill, referred to as the maximum change of the pipe diameter divided by the undeformed diameter, is an important parameter in the design and safety check of buried pipelines. However, quantitative equations on the deflection useful for engineering practice are very limited. In this paper, a two-dimensional finite element analysis is used to investigate the peaking deflection of high-density polyethylene (HDPE) pipes. In the analyses, the pipe–soil interaction is rationally modeled. A field trial is conducted and the finite-element modeling is evaluated by using the data measured in the field test. Parametric studies are also conducted to investigate the effects of pipe diameter, pipe stiffness, soil modulus, trench width, and compactor type on the peaking deflection of buried HDPE pipes. A new estimating tool is developed that considers the major influencing factors: pipe diameter, pipe stiffness, soil modulus, and compactor type (vibratory plate or rammer) to predict the peaking deflection of HDPE pipes, and the proposed method is finally verified by data reported in published studies. The comparison of the calculated and measured peaking deflections demonstrates a reasonably good prediction of the peaking deflection.